Evaluasi Program Pengembangan Potensi Kampung Dolanan Semampir Di Kota Kediri - Anita Koesherawati; Budiman Agung Pratama; Muhammad Yanuar Rizky (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: In the study, the scope and objectives were to determine the activities of Kampung Dolanan Semampir, the planning carried out regarding the capital and strategy of Kampung Dolanan Semampir, the process of implementing the development program of Kampung Dolanan Semampir, the tourist attraction of Kampung Dolanan Semampir in Kediri City. Methods: The approach used is descriptive qualitative Desain CIPP. The data collection procedures were observation, interviews, and documentation with the subject of the chief manager, treasurer, head of youth organization, and tourists. Data analysis is qualitative with the stages: data reduction, data display and conclusions and using the validity of the findings checking. Results: The scope and purpose of eliminating the negative image as a former localization turned into an educational village (preserving traditional games). Regarding capital planning, namely from community self-help and cooperation from outside parties, the process of implementing improvements to existing facilities and infrastructure then involving several agencies in the development process, one of which is a salt warehouse in the form of financial assistance and sportsmanship, making the surrounding residents to promote MSMEs as additional economic income for the surrounding community. Finally, to attract tourists, by promoting through social media, door-to-door filling activities in the Kediri City park or CFD joint gymnastics, holding workshops for the production of children's games, learning Javanese language, and making traditional dishes. Conclusions: Introducing traditional games so that they are not too dependent on gadgets, and can apply them in daily life in activities, one of which is able to improve health.